EFFICACY OF ENDOSCOPIC THIRD VENTRICULOSTOMY IN NONCOMMUNICATING HYDROCEPHALUS - Haq, Mian Iftikhar ul; Khan, Shahbaz Ali; Raja, Riaz A; Ahmed, Ehtisham (Journal of Ayub Medical College Abbottabad, 2012)
Background: Hydrocephalus is common problem requiring either extra-cranial (shunts) or intracranial (ventriculostomy) diversion of cerebrospinal fluid. Endoscopic third ventriculostomy obviates all the complications of shunts and has been accepted as the procedure of choice for the treatment of obstructed hydrocephalus in adults and children because of the minimally invasive nature. This study was conducted to determine the efficacy of endoscopic third ventriculostomy in the treatment of noncommunicating hydrocephalus. Methods: This cross sectional descriptive study was done in neurosurgery department of Hayatabad Medical Complex, Peshawar, from 2nd February 2011 to 1st march 2012. A total of 171 patients with non-communicating hydrocephalous, irrespective of gender discrimination and Glasgow coma scale score of 10 and above were included in this study. Patients below one year of age, with lesion in the floor of the third ventricle or near basilar artery, and hydrocephalus with infected CSF or haemorrhage were excluded. Hydrocephalous was diagnosed on CT-scan brain. All the patients were followed up till 72 hours post-operatively for the determination of effectiveness in terms of improvement in Glasgow coma scale by at least 2 points. All the above mentioned information including name, age, gender and address were recorded in a predesigned proforma. The data was analysed using SPSS-17. Frequency and percentage was calculated for categorical variables. Mean±SD was calculated for age. Results: A total of 171 patients with noncommunicating hydrocephalous were included in the study. Out of 171 patients, there were 104 (60.8%) males and 67 (39.2%) females. Age ranged from 1-70 years with majority of the patients was below 10 years of age. Majority of the patients had hydrocephalus due to tuberculous meningitis 39.2% of the whole. In 134 (78.4%) patients the procedure was effective. Procedure was more effective in hydrocephalus due to space occupying lesion. Conclusion: Endoscopic third ventriculostomy is a very effective procedure for the treatment of non-communicating hydrocephalus. Keywords: Endoscopic third ventriculostomy, non-communicating hydrocephalus, effectiveness, shunt